2020
DOI: 10.3390/jrfm13020026
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Economic Freedom on Economic Growth? New European Dynamic Panel Evidence

Abstract: This paper analyzes the impact of economic freedom along with traditional economic factors on economic growth for a panel of European countries. The growth of the gross domestic product was observed over a twenty-year time period on a sample of 43 developing and developed countries. Based on a robust dynamic panel setting, we conclude that increases in economic freedom as expressed by the Index of Economic Freedom/Heritage Foundation (but not its levels) are related to economic growth. The EU membership status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…K. Gehring (2013) confirmed the positive impact of economic freedom on subjective well-being, I. Brkić et al (2020) and L. Mura et al (2017) examined economic freedom and economic growth. C. Williamson and R. L. Mathers (2011) also examined the impact of economic freedom and culture on economic growth.…”
Section: Literature Reviewmentioning
confidence: 80%
“…K. Gehring (2013) confirmed the positive impact of economic freedom on subjective well-being, I. Brkić et al (2020) and L. Mura et al (2017) examined economic freedom and economic growth. C. Williamson and R. L. Mathers (2011) also examined the impact of economic freedom and culture on economic growth.…”
Section: Literature Reviewmentioning
confidence: 80%
“…Recently, in an empirical analysis for 43 European countries between 1995 and 2014, the authors concluded that economic freedom has a positive effect on economic growth, with increases in economic freedom scores positively impacting said growth [9]. Dissonant to most researchers who find positive correlations between economic freedom and economic growth, a small number of researchers argue that high levels of economic freedom can be detrimental to economic growth.…”
Section: Literature Review and Hypothesis Formulation 21 Economic Freedommentioning
confidence: 99%
“…The countries have economic structures with different levels of economic freedom in the world. Therefore, the effect of economic freedom on economic growth and development has been widely researched in the related literature and a positive effect of market-oriented economic structures on economic growth and development has been mainly revealed [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%